Resenha de: Economic Systems and Society - Januário Francisco Megale (Revista de História, 1975)
DALTON  (George). — Economic Systems and Society. Capitalism, Communism and the Third World.  Harmondworth (Inglaterra), Penguin Books, 1974, 250 pp.